FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Puput Pujiati; Viriany Viriany (Jurnal Paradigma Akuntansi, 2023)
The purpose of this research is to obtain empirical evidence about the effects of Leverage, firm size, profibility, on cash holding of the manufacturing companies listed in Indonesia Stock Exchange in the period of 2017-2019. This study used 58 manufacturing companies as data and were selected using purposive sampling technique. he research data is managed using Eviews software version 10. The results of this research show that leverage has no significant negatif effect on cash holding while firm size have no significant positif effect on cash holding,This research also indicates that profitability has a significant positif effect on cash holding.